Effect of Nigella sativa seed extract on estradiol, FSH levels, and vaginal maturity index in menopausal women: A randomized controlled trial - Sukatendel, Khairani; Hasibuan, Reni H.; Siregar, Muhammad FG.; Faradina, Dwi; Edianto, Deri; Lintang, Letta S.; Rusda, Muhammad; Inriani, Vega (Narra J, 2025)
Nigella sativa seed extract has been shown to have a significant effect on endometrial thickness and vaginal cytology in ovariectomized animal models, suggesting potential benefits for managing menopausal symptoms. However, to the best of the author’s knowledge, no human studies have been done to support these conclusions. The aim of this study was to investigate the effects of N. sativa seed extract on estradiol, follicle-stimulating hormone (FSH), and the vaginal maturity index (VMI) in postmenopausal women. A single-blinded, randomized placebo-controlled experiment was carried out at Haji Adam Malik Hospital, Medan, Indonesia, with 50 eligible postmenopausal women patients randomized into three groups. Group 1 received a placebo, while groups 2 and 3 were given N. sativa seed extract at 910 mg/day and 1,365 mg/day, respectively. All participants were blinded to the treatment they received. The study used Shad Nigella Plus, an Indonesian herbal medicine containing 455 mg of N. sativa seed extract per capsule. Before the treatments, estradiol levels, FSH levels, and VMI were measured at baseline and remeasured after eight weeks of treatment. Two participants in the intervention group withdrew due to nausea, a reported side effect of N. sativa seed extract consumption. Both treatment groups showed significant increases in estradiol levels (p=0.01 and p=0.001) and VMI (p=0.004 and p=0.001) after eight weeks of daily N. sativa seed extract administration compared to the placebo group. However, no significant differences were found between the two doses in estradiol levels and VMI (p=0.12 and p=0.673, respectively). Moreover, FSH levels showed no significant difference throughout both interventions (p=0.53 and p=0.96, respectively). In conclusion, twice-daily N. sativa seed extract at 910 mg/day or 1,365 mg/day for eight weeks significantly increased estradiol levels and VMI in menopausal women but had no significant effect on FSH levels. These findings support the potential role of N. sativa seed extract as a natural treatment for menopausal symptoms.